Compound focusing mirror and X‐ray waveguide optics for coherent imaging and nano‐diffraction. (24th June 2015) - Salditt, Tim; Osterhoff, Markus; Krenkel, Martin; Wilke, Robin N.; Priebe, Marius; Bartels, Matthias; Kalbfleisch, Sebastian; Sprung, Michael
<x xml:space="preserve">Abstract</x> A compound optical system for coherent focusing and imaging at the nanoscale is reported, realised by high‐gain fixed‐curvature elliptical mirrors in combination with X‐ray waveguide optics or different cleaning apertures. The key optical concepts are illustrated, as implemented at the Göttingen Instrument for Nano‐Imaging with X‐rays (GINIX), installed at the P10 coherence beamline of the PETRA III storage ring at DESY, Hamburg, and examples for typical applications in biological imaging are given. Characteristic beam configurations with the recently achieved values are also described, meeting the different requirements of the applications, such as spot size, coherence or bandwidth. The emphasis of this work is on the different beam shaping, filtering and characterization methods.